2022
DOI: 10.1108/ijchm-05-2022-0587
|View full text |Cite
|
Sign up to set email alerts
|

Examining tour guide humor as a driver of tourists’ positive word of mouth: a comprehensive mediation model

Abstract: Purpose Tour guides often use humor to entertain tourists, but the process of tour guide humor (TGH) affecting tourists’ positive word of mouth (PWOM) remains unclear. To fill the gap, this study aims to investigate how TGH enhances tourists’ PWOM through perceived relationship investment, perceived wellness value and trust in tour guides. Design/methodology/approach A comprehensive mediation model was proposed based on social exchange theory (SET). Data were obtained from 335 tour group tourists and analyze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 51 publications
(151 reference statements)
0
4
0
Order By: Relevance
“…In the tourism context, returning to a tourist destination and recommending it to others are the best proof of tourism loyalty [14], so tourism loyalty generally includes the dimensions of intention to recommend and revisit intention [33,37]. Furthermore, studies have shown that tour guides who incorporate humor into interpretation have a positive impact on tourists' inclination to engage in positive word-of-mouth about their experiences [21]. Cheng et al (2019) surveyed 562 Chinese mainland tourists visiting Taiwan, and found that tour guide interpretation positively influences tourists' revisit intention [31].…”
Section: Literature Review and Hypothesis Development 21 Tour Guide I...mentioning
confidence: 99%
See 1 more Smart Citation
“…In the tourism context, returning to a tourist destination and recommending it to others are the best proof of tourism loyalty [14], so tourism loyalty generally includes the dimensions of intention to recommend and revisit intention [33,37]. Furthermore, studies have shown that tour guides who incorporate humor into interpretation have a positive impact on tourists' inclination to engage in positive word-of-mouth about their experiences [21]. Cheng et al (2019) surveyed 562 Chinese mainland tourists visiting Taiwan, and found that tour guide interpretation positively influences tourists' revisit intention [31].…”
Section: Literature Review and Hypothesis Development 21 Tour Guide I...mentioning
confidence: 99%
“…Similarly, Syakier and Hanafiah (2022) gathered data from 384 tourists in Kuala Lumpur, Malaysia, and found that tour guide performance and tourist satisfaction positively influence their behavioral intention, which subsequently affects their willingness to revisit and the reputation of the destination [20]. Additionally, Fu et al (2023) conducted research indicating that the interpretation humor displayed by tour guides can effectively promote positive word-of-mouth from tourists [21].…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have identified it as a multi-dimensional concept, including switching cost (SWC), alternative attractiveness (AA) and relational investment (Koo et al, 2020). The social exchange theory posits that relationships between different entities are determined by the trade-off analysis between their subjective cost and reward appraisals (Fu et al, 2023). SWC, as a cost factor, relates to the psychological or financial burden when leaving a current service provider.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Cultural tourists receive service from the tour guides accompanying them in the language they prefer while learning about the historical, artistic, environmental, natural, and cultural assets of the destinations and historical sites visited (Akgunduz & Eser, 2022;Douglas, Hoogendoorn, & Richards, 2023;Hwang & Lee, 2019;Latkova, Jordan, Vogt, Everette, & Aquino, 2020;Mousa, Abdelgaffar, Salem, Elbaz, & Chaouali, 2023;Weiler & Black, 2021). Tour guides shape the destination experiences of tourists, bringing value and meaning to the overall experience (Cheng, Kuo, Chang, & Chen, 2019;Huang, Hsu, & Chan, 2010;Nour Salah Al-Okaily Alzboun, & Abuhjeeleh, 2023) while impacting tourists' satisfaction levels and behavioral intentions (Chang, 2014;Cheng et al, 2019;Fu, Li, XU, Liu, & Chen, 2023;Huang et al, 2010;Zeng & Yi Man Li, 2021). For this reason, another aim of this study is to examine the moderating role of tour guide competence in the relationship between the perceived value, satisfaction levels, and behavioral intentions of tourists in the context of cultural tours.…”
Section: Introductionmentioning
confidence: 99%